2021
DOI: 10.3390/jcm10071394
|View full text |Cite
|
Sign up to set email alerts
|

Subthreshold Diode Micropulse Laser Combined with Intravitreal Therapy for Macular Edema—A Systematized Review and Critical Approach

Abstract: Objective: intravitreal therapy for macular edema (ME) is a common clinical approach to treating most retinal vascular diseases; however, it generates high costs and requires multiple follow-up visits. Combining intravitreal anti–vascular endothelial growth factor (VEGF) or steroid therapy with subthreshold diode micropulse laser (SDM) application could potentially reduce the burden of numerous intravitreal injections. This review sought to explore whether this combination treatment is effective in the course … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…[32][33][34] Recently, Gawecki published a systematic review about subthreshold MPL combined with intravitreal injections in macular edema treatment. 35 Analysing different studies about MPL and anti-VEGF in DME, 32,34,[36][37][38][39] author concluded that combining MPL would reduce the number of required intravitreal injections in cases of limited macular edema with non-inferior functional and morphological outcomes to those of anti-VEGF monotherapy, as observed in our study. Of course, author suggested that larger randomized trials were need to delineate the exact role of MPL in the treatment of DME.…”
Section: Discussionsupporting
confidence: 67%
“…[32][33][34] Recently, Gawecki published a systematic review about subthreshold MPL combined with intravitreal injections in macular edema treatment. 35 Analysing different studies about MPL and anti-VEGF in DME, 32,34,[36][37][38][39] author concluded that combining MPL would reduce the number of required intravitreal injections in cases of limited macular edema with non-inferior functional and morphological outcomes to those of anti-VEGF monotherapy, as observed in our study. Of course, author suggested that larger randomized trials were need to delineate the exact role of MPL in the treatment of DME.…”
Section: Discussionsupporting
confidence: 67%
“…Although a lower incidence of complications was reported with SML treatment compared with conventional laser treatment, SML treatment has not shown superior effectiveness [31][32][33][34]. However, the use of a combined treatment may be an effective and safe alternative for ME treatment and may reduce the number of intravitreal anti-VEGF injections required [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Gawęcki and colleagues performed a systematized review and proposed that combining the SML treatment with anti-VEGFs may require fewer intravitreal injections than anti-VEGF monotherapy with equally favorable functional and morphological results in the ME treatment. However, SML alone was not superior to intravitreal treatment alone or combined treatment [33]. The authors noted that the studies under review varied in treatment protocols and inclusion criteria [33].…”
Section: Diabetic Macular Edemamentioning
confidence: 99%
See 1 more Smart Citation
“…Laser can improve retinal oxygenation, decrease vascular leakage and reduce macular edema. 9 In addition, anti-VEGF agents like ranibizumab (Lucentis ® , Novartis, Basel, Switzerland) can inhibit angiogenesis and reduce leakage and macular edema, but the main drawback of these agents that they require multiple injections to maintain a stable effect. 10 …”
Section: Introductionmentioning
confidence: 99%